Metastatic Carcinoma of Unknown Primary Presenting as Jugular Venous Thrombosis. (6th December 2009) - Modayil, Prince Cheriyan; Panthakalam, Sathyan; Howlett, David C.
Abstract : Jugular venous thrombosis is unusual and is associated with central venous catheterisation, intravenous drug abuse and head and neck sepsis. It is rarely associated with malignancy. We report a case of metastatic carcinoma of unknown primary in a forty year old female which presented with jugular venous thrombosis. The discussion includes investigation and treatment options for this condition.